PEM water electrolyzer modeling: Issues and reflections - Abdelkrim Benmehel; Salaheddine Chabab; Arthur Lucas Do Nascimento Rocha; Michael Chepy; Tarik Kousksou (Energy Conversion and Management: X)
Nowadays, water electrolysis is widely recognized as a crucial step in the transition towards a hydrogen-based economy. Several technologies are available for water electrolysis, and polymer electrolyte membrane (PEM) water electrolyzer offers numerous benefits such as high efficiency, quick response to fluctuations in renewable energy sources, capability to function under high pressure, modular design, ability to handle high current density, and production of high-purity hydrogen with minimal water usage. Numerous modeling methods have been developed in the research literature to describe the operation and performance of PEM electroyzers. Each model has its own advantages and limitations, and is only valid under certain assumptions and running conditions. This article aims to provide an in-depth review of the main factors affecting the performance of PEM technology, as well as provides a comprehensive analysis of PEM system modeling, covering different thermodynamic, electrochemical, energy, momentum, and mass models, and finishing with the physical modeling challenges for PEM technology.